The natural gas potential of Saudi Arabia. Issue 18 (16th September 2016) - Demirbas, Ayhan; Alsulami, Hemaid; Nizami, Abdul-Sattar
ABSTRACT: Kingdom of Saudi Arabia (KSA) has the fourth largest natural gas (NG) reserves in the world. One third of these reserves are located in the Ghawar region of Eastern Province. NG production is controlled tightly due to close conjunction with oil production until recently. KSA's NG production of 85 billion cubic meters in 2015 from 70 billion cubic meters in 2008 sets an average annual increase of 2.7%. More than half of the annual KSA's NG production has been accompanied by gas. The Saudi Gas Initiative (SGI) aims to increase foreign investment in the NG development sector through petrochemicals, power generation, and gas development while integrating with salt water desalination. The barriers in the success of motor fuel policies include high initial capital costs, lack of information or skills, less market acceptance, technology limitations, and financing risks. This article aims to review the potential of NG as an alternative to oil and coal in KSA in meeting the country's high energy requirements.